New Testament exegesis a handbook for students and pastors - Fee, Gordon Donald, 1934- (Louisville, KE Westminster/John Knox, 1993)
Includes bibliographical references and indexes.
First edition published 1983.
Keywords: Bible. N.T. -- hermeneutics -- handbooks, manuals, etc